Characterisation of the pre-invasion glycophosphatidylinositol-anchored surface proteins of Plasmodium falciparum merozoites - Cromarty, Allan Duncan (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.